5, 6-Benzoflavones as cholesterol esterase inhibitors: synthesis, biological evaluation and docking studies12. Issue 3 (8th February 2018) - Singh, Jatinder V.; Kaur, Anumeet; Bhagat, Kavita; Gupta, Manish K.; Singh, Manwinder; Singh, Harbinder; Bedi, Preet Mohinder S.
Abstract : A library of forty 5, 6-benzoflavone derivatives was synthesized and evaluated for their inhibitory potential against cholesterol esterase (CEase) enzyme. Abstract : In a continued effort to develop potent cholesterol esterase (CEase) inhibitors, a series of 5, 6-benzoflavone derivatives was rationally designed and synthesized by changing the position of the benzene ring attached to the flavone skeleton in previously reported 7, 8-benzoflavones. All the synthesized compounds were checked for their inhibitory potential against cholesterol esterase (CEase) using a spectrophotometric assay. Among the series of forty compounds, seven derivatives (B -10 toB -16 ) exhibited above 90 percent inhibition against CEase in an in vitro enzymatic assay. CompoundB -16 showed the most promising activity with an IC50 value of 0.73 nM against cholesterol esterase. To determine the type of inhibition, enzyme kinetic studies were carried out forB -16, which revealed its mixed-type inhibition approach. Moreover, to figure out the key binding interactions ofB -16 with the amino acid residues of the enzyme's active site, molecular protein–ligand docking studies were also performed.B -16 completely blocks the catalytic assembly of CEase and prevents it from participating in the ester hydrolysis mechanism. The favorable binding conformation ofB -16 suggests its prevailing role as a CEase inhibitor. Overall, the study showed that the cis -orientation of ring A with respect to the carbonyl group of ring C is responsible for the potent CEase inhibitory activity of the newly synthesized compounds.